2006
DOI: 10.1002/jnr.21020
|View full text |Cite
|
Sign up to set email alerts
|

Murine neocortical histogenesis is perturbed by prenatal exposure to low doses of bisphenol A

Abstract: Bisphenol A (BPA) has been shown to disrupt thyroid hormone function. We therefore studied whether prenatal exposure to low-doses of BPA affects the morphology and the expression of some genes related to brain development in the murine fetal neocortex. Pregnant mice were injected subcutaneously with 20 microg/kg of BPA daily from embryonic day 0 (E0). Control animals received vehicle alone. For evaluating cell proliferation, neuronal differentiation and migration, bromodeoxyuridine (BrdU) was injected intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 32 publications
3
58
0
1
Order By: Relevance
“…138 In addition, BPA exposure alters neocortical histogenesis in the mouse. 139,140 Although no specific link was made to TH action in this study, the findings are consistent with the hypothesis that BPA alters early development of the cortex by interfering with TH signaling.…”
Section: Bisphenol-asupporting
confidence: 79%
“…138 In addition, BPA exposure alters neocortical histogenesis in the mouse. 139,140 Although no specific link was made to TH action in this study, the findings are consistent with the hypothesis that BPA alters early development of the cortex by interfering with TH signaling.…”
Section: Bisphenol-asupporting
confidence: 79%
“…Nakamura et al (2006), supported by grants from the Japanese government, examined the effects of prenatal exposure to bisphenol A on the morphology and expression of certain genes related to brain development in the mouse neocortex. In the first experiment ICR/Jc1 mouse dams were injected subcutaneous with either 0 (sesame oil vehicle) or 20 m/kg bw/day bisphenol A [purity not indicated] daily from GD 0 (defined as the day that a vaginal plug was detected) until GD 10.5, GD 12.5, GD 14.5 or GD 16.5.…”
Section: [No Additional Information Was Provided For Statistical Analmentioning
confidence: 99%
“…Impairment by bisphenol A of sexual differentiation of exploratory behavior and the size of the locus coeruleus was also observed [27], and it also increased depression-like behavior [28]. Furthermore, neocortical histogenesis was perturbed by bisphenol A [29]. We have demonstrated that rat hyperactivity was elicited by bisphenol A via both intracisternal administration [4] and oral administration to 5-day-old Wistar pups [5].…”
Section: Discussionmentioning
confidence: 74%